Evaluation of the Building Together Mutual-Aid-Housing Project in Bangkok - Zilla C. Phoativongsacharn; Archer, Raymon W.; Kammeier, Hans Detlef; Tips, Walter E. J.; The Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1984)
The Building together Project in Bangkok is a two-part project, the first part consisting of low-income housing using mutual-aid labor and the second part consisting of contractor-built housing for sale at market prices to middle-income families. The latter serve as a cross-subsidy to the former, which have been sold to participating families at prices below cost. The mutual-aid part of the Project is the focus of this study. Survey findings indicate that participants enjoy living conditions that are an improvement over conditions in their former places of residence. Recent developments also indicate that mutual-aid work bas contributed towards welding the participating families into a strong community. However, a combination of unplanned for expenditures, inflation, inefficiencies due mainly to difficulties in managing mutual-aid labor, and delays due to external factors have served to increase costs of the mutual-aid housing. This has in turn necessitated the expansion of the cross-subsidy part of the project as a measure to achieve the recovery of historical costs. The study gives recommendations for action, in light of the Building Together experience, that could be undertaken in future projects aiming to use mutual aid and to achieve cost recovery. The need for governmental assistance in the areas of building regulations, housing development procedures and financing for the success of such projects is emphasized.
A thesis submitted in partial fulfillments oi the requirements for the degree of Master or Science
Thesis (M.Sc.) - Asian Institute of Technology, 1984
Keywords: Self-help housing -- Thailand -- Bangkok